2021
DOI: 10.1021/acs.jproteome.1c00406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metabolite and Lipid Association Networks Reveals Molecular Mechanisms Associated with 3-Month Mortality and Poor Functional Outcomes in Patients with Acute Ischemic Stroke after Thrombolytic Treatment with Recombinant Tissue Plasminogen Activator

Abstract: Here, we present an integrated multivariate, univariate, network reconstruction and differential analysis of metabolite–metabolite and metabolite–lipid association networks built from an array of 18 serum metabolites and 110 lipids identified and quantified through nuclear magnetic resonance spectroscopy in a cohort of 248 patients, of which 22 died and 82 developed a poor functional outcome within 3 months from acute ischemic stroke (AIS) treated with intravenous recombinant tissue plasminogen activator. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…Our ndings validated previously described changes in serum levels of ketone bodies, BCAAs, and energy compounds in acute stroke 4,18,19 . Involvement of these metabolite subclasses should come from interplay of different metabolic pathways, all triggered by cerebral vessel occlusion (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Our ndings validated previously described changes in serum levels of ketone bodies, BCAAs, and energy compounds in acute stroke 4,18,19 . Involvement of these metabolite subclasses should come from interplay of different metabolic pathways, all triggered by cerebral vessel occlusion (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that after brain injury, the expressions of citric acid, fumaric acid, and malic acid were decreased, indicating that the TCA pathway was inhibited [ 28 ]. The increased ketone body metabolism could provide alternative energy sources and to maintain free radical homeostasis during ischemia reperfusion injury [ 29 ]. 1-(4-methoxyphenyl)-4-methylpenta-1,4-pentadien-3-one, the precursor of ketone body, was significantly downregulated in MCAO model group in this experiment, which implied the ketone body metabolism was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of using metabolomics to identify differentially regulated processes related to stroke outcomes, few studies focus on this metric. In a large Italian study with over 200 available serum samples obtained within 24 h of treatment with tPA, Licari et al ( 45 ) identified only three metabolites as significantly changed between subjects with a poor 3-month functional outcome (mRS ≥3) compared to those with a good 3-month functional outcome (mRS ≤ 2) ( 45 ). These included upregulation of 3-hydroxybutyrate, Subfraction ApoB LDL-3, and LDL3_PN in patients with a good functional outcome compared to those with a poor functional outcome.…”
Section: Discussionmentioning
confidence: 99%